Long-Term Results of Open Stent-Grafting Using a Matsui-Kitamura Stent to Treat Thoracic Aortic Aneurysm - Midorikawa, Hirofumi (Ann Thorac Cardiovasc Surg, 2014)
Purpose: We describe a retrospective study of initial and long-term outcomes with an open stent grafting (OSG) with a Matsui-Kitamura stent for treating thoracic aortic aneurysm. Methods: Between August 2005 and September 2013, 50 patients with aortic arch disease extending to the descending aorta underwent OSG. Circulatory arrest with total cardiopulmonary bypass and selective cerebral perfusion were used, and the aorta was transected between the brachiocephalic and left subclavian artery. The stent-graft was inserted, sutured to a transected aortic edge, and anastomosed to a four-branched arch graft. Preoperative, operative, and short- and long-term postoperative data were obtained from the patients’ medical records. Results: The perioperative (within 30 days) mortality rate was 8%. Two patients (4%) had a stroke and 5 patients (10%) had a spinal cord injury resulting in paraplegia or paraparesis (1 patient each) or transient paraplegia (3 patients). Actuarial survival rates at 1, 3, 5, and 7 years postoperatively were 87.8%, 78.3%, 70.7%, and 65.3%, respectively; the rates of freedom from an aortic event were 100%, 89.1%, 82.2%, and 74.7%. There were no complications related to use of the stent-graft. Conclusion: Our OSG method provided durable results in patients treated for thoracic aortic aneurysm, with few adverse events.